Hemodynamic Features of Cesarean Section Patients with Spinal Anesthesia - Alan Marbase, Festus; Susanto, Amin; Mixrova Sebayang, Septian (Global Indonesia Health Care (GOICARE), 2024)
Background: Sectio Caesarea (SC) surgery in labouring women can lead to haemodynamic risks. One of the haemodynamic events is a drop in blood pressure, this is the effect of spinal anaesthesia. Purpose: To determine the haemodynamic features of sectio sesarea patients with spinal in the operating room of RSUD Yowari Jayapura Regency. Methods: This research design uses descriptive design. Sampling technique with total sampling of 40 SC patients. The research instrument contains patient data which includes age, blood pressure, heart rate, breathing, and body temperature. Findings: The average age of patients obtained was 30.38, systolic before 129.32 and after 94.90, diastolic before 90.48 and after 59.38, heart rate before 84.70 after 118.90, breathing before 18 after 18.70, body temperature before 36.350C after 36.420C, MAP before 180.95 after 134.53 while oxygen saturation before 98.93 and after 99.15. Conclusion: There are haemodynamic events in SC patients after surgery at Yowari Hospital, Jayapura Regency.